Efektivitas Dry Needling Terhadap Nyeri Punggung Bawah: Literature Review - Karinina Zahwa Putri Prasetyo; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Low back pain (LBP) is one of the most common musculoskeletal complaints affecting the spinal region and can significantly interfere with daily activities while reducing long-term functional capacity. Management strategies targeting myofascial trigger points (MTrPs) often require safe and effective physiotherapeutic approaches. One technique that has been widely investigated is dry needling (DN), which involves inserting a fine needle into the MTrP to elicit a local twitch response that may reduce pain and improve muscle performance. This study aims to analyze the effectiveness of DN in reducing pain and enhancing function in patients with non-specific low back pain, based on ten randomized controlled trials (RCTs) published between 2020 and 2024. Data were obtained from PubMed, ScienceDirect, and Google Scholar. The findings indicate that DN significantly decreases pain intensity, increases pressure pain threshold (PPT), and improves disability scores (ODI). The therapeutic effects of DN are greater when combined with core stabilization exercises or spinal manipulation therapy. DN is also considered safe, with only minor and transient adverse effects such as localized soreness.